Confronting the financial crisis: surveillance and regulation - Roncaglia, Alessandro (PSL Quarterly Review, 2010)
The article is an introduction to the new issue of the Journal. It provides an overview of the current economic and financial situation and summarises the main topics dealt with by the following articles. The financial crisis continues to unfold, taking new turns. By now, it is clear that bank bailouts have a heavy cost for the public purse. This adds to the usual increase in public deficits in periods of economic crisis. Financial markets price these difficulties in terms of wider spreads between bills and bonds of such countries compared to “safe” countries such as Germany. In turn, this increases the cost of public debt and risks igniting an unsustainable downward spiral. Recourse to heavy cuts in public expenditure is called forth by some powerful European governments and by the remnants of the Washington consensus; however, under the pressure of financial markets even those who are not convinced by the validity of this policy strategy have to give in. Thus, the costs of banking bailouts are shifted onto social expenditure, while the general retrenchment of the public sector aggravates the economic crisis. JEL Codes: G01, G21, N20